ANALYSIS OF MONTHLY GLOBAL SOLAR RADIATION IN ERBIL-IRAQ - Ibrahim, Hassan S. (Science Journal of University of Zakho, 2024)
Solar energy is a crucial and sustainable source of electricity that may be harnessed for a long duration without causing pollution. Moreover, it reduces pollution, thus improving the quality of life and reducing the cost of energy in the long term. This study analyzes and uses the modified Angstrőm–Prescott equation to estimate the monthly average global solar radiation in the Erbil governorate depending on latitude and daylight hours. The data is collected from the Agriculture Directorate in Erbil for ten stations in different locations for the period (2016-2023). Results show that the global solar energy in the region reaches a maximum of   8.4 kW.day-1.m-2 in the summertime and descends to a minimum of 1.6 kW.day-1.m-2 in winter. The equation used to estimate global solar energy is in strong agreement with measured data from the ground base weather station, and to validate the results, mean absolute percentage error (MAPE) and residual mean square error (RMSE) were used. They found the value of MAPE = 4.34 -7.98 and RMSE= 0.183-0.426, indicating that the model is suitable for estimating solar radiation.
Keywords: Estimation; Erbil; Extraterrestrial; Global; Solar energy